Antiseptic efficacy of an innovative perioperative surgical skin preparation: A confirmatory FDA phase 3 analysis. (June 2020) - Edmiston, Charles E.; Lavin, Philip; Spencer, Maureen; Borlaug, Gwen; Seabrook, Gary R.; Leaper, David
Abstract: Background: An innovative approach to perioperative antiseptic skin preparation is warranted because of potential adverse skin irritation, rare risk of serious allergic reaction, and perceived diminished clinical efficacy of current perioperative antiseptic agents. The results of a confirmatory US Food and Drug Administration (FDA) phase 3 efficacy analysis of a recently approved innovative perioperative surgical skin antiseptic agent are discussed. Methods: The microbial skin flora on abdominal and groin sites in healthy volunteers were microbiologically sampled following randomization to either ZuraGard, a 2% chlorhexidine/70% isopropyl alcohol preparation (Chloraprep), or a control vehicle (alcohol-free ZuraGard). Mean log10 reduction of colony-forming units (CFU) was assessed at 30 seconds, 10 minutes, and 6 hours. Results: For combined groin sites (1, 721 paired observations) at all time points, the mean log10 CFU reductions were significantly greater in the ZuraGard group than in the Chloraprep group ( P < .02). Mean log10 CFU reductions across combined abdominal and groin sites at all time points (3, 277 paired observations) were significantly greater in the ZuraGard group than in the Chloraprep group ( P < .02). Conclusions: A confirmatory FDA phase 3 efficacy analysis of skin antisepsis in human volunteers documented that ZuraGard was efficacious in significantly reducing the microbial burden on abdominal and groin test sites, exceeding that of Chloraprep. No significant adverse reactions were observed following the application of ZuraGard. Trial registration: ClinicalTrials.gov identifiers: NCT02831998 and NCT02831816.